Pola Asuh dalam Pandangan Zainuddin Fananie - Ratu Kemala; Illa Susanti; Asep Muharam; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2022)
This study aims to discuss the parenting style in Zainuddin Fananie's view. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is Zainuddin Fananie's modern education, while the material object is Islamic parenting. The results and discussion of this study indicate that Zainuddin Fananie's view of parenting for children at home emphasizes the education of the spirit, mind, and body. This study concludes that parenting in Zainuddin Fananie's view emphasizes compassion which is related to objectivity and wisdom.